Can university social responsibility improve student satisfaction through service quality? - Suranta, Sri; Setiadi, Fahmi; Karunia, Asaprima Putra; Wulandari, Trisninik Ratih (Journal of Contemporary Accounting, 2024)
This research explored the importance of university social responsibility (USR) as an implemented strategy for improving service quality and student satisfaction. Specifically, it sought to investigate the impact of USR on student satisfaction through the mediating factor of service quality. The population comprised all students of the Economics and Business Faculty at Universitas Sebelas Maret (UNS) Surakarta, a state institute. The samples were drawn from students in their fifth semester and beyond, as these students were believed to have a deeper knowledge of the USR activities conducted by the institution, compared to those in their first semester. The variables used are: (1) USR application as the independent variable, (2) service quality as the mediating variable, and (3) student satisfaction as the dependent variable. The data collection started with preparing the tools and information to estimate all the included variables. The questionnaire was made using Google Docs, and a related link was generated for distribution. The respondents then completed the questionnaire, and the data were gathered in a database, and later downloaded in Excel or another format, depending on the statistical analysis tool used. Path analysis was done to test the hypotheses using the WarpPLS 8.0 statistical tool. The results indicated that service quality mediated the USR effect on student satisfaction. Notably, the coefficient values revealed that the indirect USR effect on student satisfaction, through service quality, was stronger than the direct effect. While some prior models have researched the relationship between corporate social responsibility (CSR) and consumer satisfaction, this study applies the concept of USR in education, using a distinct set of measurements.